BENTUK MORFOSEMANTIK DALAM TEKS TRADISI LISAN NYIANG LENGAN PADA MASYARAKAT DAYAK MAANYAN DI KALIMANTAN TENGAH - Intan Ayu Puspita; I Nyoman Weda Kusuma; I Made Suastika (Program Magister Linguistik Universitas Udayana, 2018)
Nyiang Lengan is an oral tradition of the Dayak Maanyan tribes in Central Kalimantan, especially in East Barito Regency. This tradition is composed of the literary language which is sung by using Pangunraun language. This research uses a morphosemantic study to understand the morphological form and its significance. Nyiang Lengan is reviewed since the writer would like to preserve the culture of Dayak Maanyan tribes and also introduce this tradition to the younger generation so that they will realize the importance of this oral tradition for the Dayak Maanyan people. It is because many young generations of Dayak Maanyan can not sing it even understand the messages of Nyiang Lengan. This research focuses on affixation and significance in the text of Nyiang Lengan. Affixation becomes the main topic to find out the morphological changes in the text of the oral tradition. Afterwards, understanding the significance is also important so that the messages of Nyiang Lengan can be delivered.